Efficient method of constructing parameters in R-ate paring - LI Bin; WANG Xin-mei (Tongxin xuebao)
In order to accelerate the computing of Tate paring, a new technique of selection method of parameters （A,B） based on R-ate technique had been proposed. Compared to Atei, this method substitutes pmmodr with pmodr in Miller loop, and p was the character of Tate pairing’s field. Could bring an advance of a larger reduction of Miller loop comparing with Atei algorithm by parameters （pi, r）, but it must constraint that field of definitions of p, So at the end, the classical selection rule of p was shown in response for improving the reliability of the method.